Prevention and prevarication: the fits and starts of prevention in the USA. Issue 4 (November 2018) - Lab, Steven
Abstract Crime prevention and its discourse in the USA has been a series of fits and starts since at least the late 1990s. There continues to exist an absence of any driving force giving direction to a true prevention movement. Most major initiatives that could be considered "prevention" tend to be gut level responses by criminal justice system actors to address existing offending (tertiary prevention) rather than identifying emerging opportunities or prospective problems and developing/initiating true primary or secondary preventive actions. When attempts are made to eliminate initial acts or opportunities to act, there is a marked lack of follow through, leaving only halfhearted attempts. This article attempts to illustrate this failure and the reasons for the failure, and makes suggestions for improving primary and secondary prevention in the future.